El aprendizaje cooperativo en la enseñanza de Lengua y Literatura para estudiantes de séptimo año de la Unidad Educativa Lauro Damerval Ayora - Yanza Sigcho, Brayan Ariel (2024)
The research entitled: Cooperative Learning in the Teaching of Language and Literature has as a general objective to determine the incidence of cooperative learning in teaching Language and Literature on seventh-year students of EGB at Lauro Damerval Ayora high school, period 2022-2023. Three specific objectives were developed: The first was to identify the characteristics of cooperative learning in teaching Language and Literature on seventh-year students from Lauro Damerval Ayora High School. The second was to design a facilitator guide for applying cooperative learning in the teaching of Language and Literature. Finally, the third was to Evaluate the application of the facilitator guide of cooperative learning in teaching Language and Literature. To carry out this study, a descriptive type of research was used with a mixed approach and quasi-experimental design. The inductive, deductive, analytical, and synthetic methods were applied during the process. In addition, the techniques that were used to carry out this research were direct observation, interview, survey, and evaluation. In the same way, the instruments used were the observation sheet, a structured-question questionnaire, and a knowledge questionnaire, so they contributed significantly to data collection. The research population wasfrom Lauro Davermal Ayora High School, from which 32 students and a teacher were selected through a non-probabilistic sampling for convenience. It is essential to mention that the cooperative learning strategy contributes significantly to the teaching and learning process of the contents. Also, it was evidenced by the application of the didactic proposal that using cooperative learning models helped students develop an understanding better approach to the knowledge imparted.